Reaching consensus via coordinated groups - Aguilar, Emerico H. (Animo Repository, 2021)
Models of opinion dynamics have been used to depict how the opinions of agents within a social network evolve based on their interconnections and interactions. The collective behaviour of agents can also exhibit certain social phenomena such as convergence to a consensus or disagreement. In this study, we propose a gossip-based model for the opinion dynamics of interconnected groups and describe how they can reach consensus. Through analysis of the convergence properties of its expected dynamics, we show that the number of groups can affect the rate by which the network reaches consensus. We also include numerical examples to demonstrate our proposed model and its properties.